2015
DOI: 10.1007/s00405-015-3670-1
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck solitary fibrous tumors: a rare and challenging entity

Abstract: The objective of this study is to analyze the outcome of treatment for solitary fibrous tumors (SFTs) in the head and neck area. SFTs present as slow-growing masses, often with local compressive symptoms that are difficult to distinguish from other soft-tissue tumors. SFTs are commonly treated using local excision without adjuvant therapy. To date, only heterogeneous small series have been published, documenting the treatment results and outcome with these tumors. Retrospective study of patients with histopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 40 publications
3
57
0
5
Order By: Relevance
“…Prior studies report recurrence in 2 of 13 (48), 0 of 11 (32), 1 of 12 (49), 2 of 8 (50), or 2 of 29 (51) head and neck SFTs, though these smaller series had predominantly shorter median follow-up. Even among a consecutive series of 9 histologically malignant solitary fibrous tumors of the head and neck reported by Yang et al only 3 recurred (52), still less than the 36% we observed.…”
Section: Discussionmentioning
confidence: 94%
“…Prior studies report recurrence in 2 of 13 (48), 0 of 11 (32), 1 of 12 (49), 2 of 8 (50), or 2 of 29 (51) head and neck SFTs, though these smaller series had predominantly shorter median follow-up. Even among a consecutive series of 9 histologically malignant solitary fibrous tumors of the head and neck reported by Yang et al only 3 recurred (52), still less than the 36% we observed.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, there is an overall good behavior with low local recurrence rate, different from other anatomic sites [39]. Although not reported in the sinonasal tract, SFTs in patients [55 years, with large tumors ([15 cm), with necrosis, increased mitotic activity and/or pleomorphism or incomplete resection are designated as ''malignant'' or ''dedifferentiated'' SFT [40,41], associated with metastasis and disease-specific mortality [42]. Treatment of sinonasal tract SFTs is usually by complete excision or by wide excision.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Safe surgical excision without breaching of the tumour capsule is considered essential to reduce the risk of local recurrence [10]. There is no conclusive evidence supporting the role of adjuvant radiotherapy or chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although local excision is usually curative, orbital SFT has occasionally been reported to recur and rarely metastasize [10]. Bernardini et al [11] reported 8 recurrences in his review of 42 cases of orbital SFTs.…”
Section: Discussionmentioning
confidence: 99%